PROSES BERPIKIR KRITIS SISWA DALAM MEMECAHKAN MASALAH PROGRAM LINEAR BERBASIS POLYA DITINJAU DARI TIPE KEPRIBADIAN HIPPOCRETES GALENUS - Indah Khoirun Nisa; Bambang Agus Sulistyono; Samijo Samijo (UPT Penerbitan Universitas Jember, 2022)
Every student has a critical thinking process that varies in difficulty. Difference personality characteristics of students influence the thinking process in mathematical problem solving. This study aims to describe each student's critical thinking process based on Polya in terms of Hippocrates Galenus' personality types: choleric, melancholic, phlegmatic, and sanguine. Linear programming is one of the materials that must be critically thought in order to solve the problem. Researchers collected data twice before analyzing the data. The findings of this study show each student's thought process was unique. 1) The Perfect Melancholy Type at Work